Back to the basics in banking? A micro-analysis of banking system stability - Olivier De Jonghe (National Bank of Belgium, 2009)
This paper analyzes the relationship between banks' divergent strategies toward specialization and diversification of financial activities and their ability to withstand a banking sector crash. We first generate market-based measures of banks' systemic risk exposures using extreme value analysis. Systemic banking risk is measured as the tail beta, which equals the probability of a sharp decline in a bank's stock price conditional on a crash in a banking index. Subsequently, the impact of (the correlation between) interest income and the components of non-interest income on this risk measure is assessed. The heterogeneity in extreme bank risk is attributed to differences in the scope of non-traditional banking activities: non-interest generating activities increase banks' tail beta. In addition, smaller banks and better-capitalized banks are better able to withstand extremely adverse conditions. These relationships are stronger during turbulent times compared to normal economic conditions. Overall, diversifying financial activities under one umbrella institution does not improve banking system stability, which may explain why financial conglomerates trade at a discount
Keywords: G12; G21; G28; 330; diversification; non-interest income; financial conglomerates; banking stability; extreme value analysis; tail risk; Kreditrisiko; Produktdifferenzierung; Arbeitsteilung; Bankenliquidität; Bankenkrise; Risikomaß; Theorie